AN ASSESSMENT OF LAND CAPABILITY AND SUITABILITY: A SUSTAINABLE PLANNING APPROACH FOR THE SINA RIVER BASIN, MAHARASHTRA (INDIA) (International Journal of Food and Nutritional Sciences, 2022)
Land capability classification serves as a vital method for judicious land use planning, which balances usage and minimizes adverse environmental effects. The Present investigation is associated with assessment of the land potential and suitability of the Sina River Basin using a geospatial approach, combining soil properties, topography, and hydrological variables. An extensive land classification wascreated through ArcGIS 10.3 using secondary data of IRS P-6 LISS-III satellite imagery, SRTM-DEM elevation models, and soil maps from NBSS & LUP. The results classify the land according to its capabilities (I to VIII), identifying areas that are viable for agriculture, pasture, forests and conservation. Class III, accounting for 49.01% of the study area, is the most extent of arable land, but requires moderate conservation due to soil and slope limitations. Classes IV, VI and VII (36.63% of the land area) is most suited for conservation, grazing or forestry, whereas Class VIII (0.38%) is not fit for any productive use. Finally, the land suitability assessment (LSA) is used to analyze the land use strategies, which categorizes the terrain according to soil depth and slope gradient. The results indicate that 35.35% of the area is very suitable for agricultural use provided adequate soil and water conservation measures are employed, while 53.05% would require measures to be kept productive. Such measures involve adopting more sustainable land management practices including contour plowing, terracing, agroforestry, and afforestation to alleviate soil erosion. The findings of this research reiterate the importance of combining remote sensing and GIS in land capability evaluation for informed decisions in resource management and environmental sustainability. Dynamic land-use modeling to account for variable climate to maximize land use in the long-term should be the focus of future studies. This evidence gives scientific grounds for decisionmakers and land managers to adopt sustainable strategic planning approaches at the local and regional levels in the Sina River Basin, and also for similar ecosystems worldwide